Talon [large type] : Combat Tracking Team - Kendig, Ronie (Kendig, Ronie. Breed apart series, 2014)
Air Force veteran Aspen Courtland just wants her brother back -- dead or alive. The US Marine Corps declared him dead, but Aspen is unwilling to let him die without a fight. Aspen adopts her brother's combat tracking team dog, Talon, hoping to come closer to finding peace about Austin. But after the brutal attack that separated dog and handler, Talon is afraid of his own shadow. Military Intelligence Operative Dane Markoski has run from the truth most of his life. Now, it's the only thing that can save him -- and his mission -- if he dares to face the past. Talon is the key to achieving his objective ... but the only way to Talon is through his new owner. But Dane swore he'd never work a woman. Teamed up in Djibouti, Dane and Aspen battle the elements and extremists. Survival depends on his skills, her optimism, and the courage of a traumatized combat tracking dog. Can Talon muster the valor for one last mission?